2009
DOI: 10.1007/s11248-009-9250-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volunteers on maize gene flow

Abstract: Regulatory approvals for deliberate release of GM maize events into the environment have lead to real situations of coexistence between GM and non-GM, with some fields being cultivated with GM and conventional varieties in successive seasons. Given the common presence of volunteer plants in maize fields in temperate areas, we investigated the real impact of GM volunteers on the yield of 12 non-GM agricultural fields. Volunteer density varied from residual to around 10% of plants in the field and was largely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 9 publications
(18 reference statements)
0
85
0
1
Order By: Relevance
“…Field observations performed on maize volunteers after GM maize cultivation in Spain revealed that maize volunteers had a low vigour, rarely had cobs and produced pollen that crosspollinated neighbour plants at low levels (Palaudelmàs et al, 2009).…”
Section: Potential For Gene Transfermentioning
confidence: 99%
“…Field observations performed on maize volunteers after GM maize cultivation in Spain revealed that maize volunteers had a low vigour, rarely had cobs and produced pollen that crosspollinated neighbour plants at low levels (Palaudelmàs et al, 2009).…”
Section: Potential For Gene Transfermentioning
confidence: 99%
“…Field observations on maize volunteers after GM maize cultivation in Spain revealed that maize volunteers had a low vigour, rarely had cobs and produced pollen that crosspollinated neighbour plants only at low levels (Palaudelmàs et al, 2009). …”
Section: (Iv) Risk Conclusionmentioning
confidence: 99%
“…The survival of maize is limited by a combination of low competitiveness, absence of a dormancy phase, and susceptibility to plant pathogens, herbivory and cold climate conditions. Maize plants are only winter hardy in European regions with mild winters, and in those situations maize kernels remaining in the field after harvest can germinate, grow, flower, and locally cross-pollinate neighbouring maize plants Palaudelmàs et al, 2009). Despite cultivation for centuries, maize plants do not occur outside cultivated or disturbed land in Europe.…”
Section: Unintended Effects On Plant Fitness Due To the Genetic Modifmentioning
confidence: 99%